Effect of socio-economic differentials on growth and development of children in five metropolitan cities of India - Marimuthu, Palaniappan; Kanmani, T R; Sowmya, K (Indian Journal of Child Health, 2016)
Background: Children’s growth and development depend on their parents’ socio-economic status. Adequate nutrition of children influence their anthropometric measures proper growth and development and reduces morbidity and mortality among children. Objective: To understand the growth and development pattern of children dwelling in the slum environment and to compare some of their growth parameters with non-slum children. Methods: This was a record review of National Family Health Survey-3 (NFHS-3) data, freely available from Measure DHS USA. Data for five major metropolitan cities, namely, Delhi, Mumbai, Kolkata, Chennai, and Hyderabad were used for this study. The households classified as slum and non-slum by two agencies, viz., NFHS and census of India were considered for analysis. Variables more relevant as an indicator for the growth and development of children, viz., height, weight, hemoglobin, standard of living index (SLI), age (in months), and place of residence were selected for this study. Place of residence (slum or non-slum) and SLI, which is proxy to socio-economic status, were considered to understand their influence on height, weight, and hemoglobin values of the children. Results: About 75% of the slum dwellers were in low SLI category, and 69% of non-slum residents were in high SLI category. There is a significant difference (p=0.001) between slum and non-slum residence on the proportions of SLI. Multivariate analysis showed that all the variables significantly differ by SLI except age of the children. Conclusion: It is concluded that the observed difference between slum and non-slum children’s height, weight, and hemoglobin are due to differences in SLI. Growth and development of children dwelling in slum or non-slum area depend on the socio-economic status of their parents and not by their place where they are growing.